PENANGANAN KASUS TINDAK PIDANA KEKERASAN SEKSUAL TERHADAP ANAK DI BAWAH UMUR DI WILAYAH HUKUM WONOGIRI - Alvian Muhammad Agil; Hanuring ayu; Nourma Dewi (Verstek, 2026)
Sexual violence against minors is one of the most serious and complex crimes in the Indonesian criminal justice system. The issue of sexual violence against minors is not only a legal issue but also  a  complex  and  multidimensional  social  problem.  A  more  comprehensive  approach  is needed,  integrating  legal,  social,  and  psychological  aspects.  This  research  is  an  empirical  legal study.  The  legal  process  for  child  sexual  violence  cases  in  Wonogiri  is  carried  out  in  an integrated  manner,  from  investigation  to  court  decision,  prioritizing  the  best  interests  of  the victim.  The  Women  and  Children  Protection  Unit  (PPA)  of  the  Wonogiri  Police  plays  an  active role  in  law  enforcement  while  providing  psychological  protection  and  coordinating  victim recovery  through  a  child-friendly  approach.  The  synergy  between  prosecutors  and  judges  in implementing  the  Child  Protection  Law  and  the  Child  Protection  and  Child  Protection  Law demonstrates  the police's commitment  to  realizing  justice  that  is  just, humane, and pro-child. Handling  child  sexual  violence  cases  in  Wonogiri  faces  complex  obstacles,  ranging  from psychological  trauma  to  social  stigma  and  limited  human  resources.  Therefore,  strengthening the protection system and strengthening the capacity of law enforcement is necessary.